Multiplex bead array assay of plasma cytokines in type 2 diabetes mellitus with diabetic retinopathy - Hang, Hui (Molecular Vision, 2014)
PURPOSE: The aim of this study was to assess the roles of plasma cytokines in diabetic retinopathy (DR) and their relationship with the severity of DR. METHODS: This study included 59 diabetic patients and 19 non-diabetic controls. The plasma concentrations of endothelial growth factor (EGF), eotaxin, fibroblast growth factor 2 (FGF-2), Flt-3 ligand (Flt-3L), fractalkine, granulocyte colony-stimulating factor (G-CSF), granulocyte–macrophage colony-stimulating factor (GM-CSF), growth-related oncogene (GRO), interferon (IFN)-α2, IFN-γ, interleukin (IL)-1α, IL-1β, IL-1Ra, IL-2, IL-3, IL-4, IL-5, IL-6, IL-7, IL-8, IL-9, IL-10, IL-12 (p40), IL-12 (p70), IL-13, IL-15, IL-17, IFN-inducible protein-10 (IP-10), monocyte chemoattractant protein (MCP)-1, MCP-3, macrophage-derived cytokine (MDC), macrophage inflammatory protein (MIP)-1α, MIP-1β, sCD40L, sIL-2Rα, transforming growth factor (TGF)-α, tumor necrosis factor (TNF)- α, TNF-β, and VEGF were measured with Luminex multiplex bead immunoassay. The levels of these cytokines were investigated according to the DR stage. RESULTS: The plasma level of ten cytokines—MCP-1, IL-6, IL-7, IL-9, IL-13, IL-15, IL-17, sCD40L, sIL-2Rα and TNF-β—increased significantly in the diabetic group compared to the controls. The Flt-3L, IL-1Ra, IL-3, IL-5, and IL-12 (p40) levels were lower in the diabetic group than in the control group. The TNF-α plasma level was significantly elevated in patients with proliferative diabetic retinopathy (PDR) compared with the levels in patients with non-proliferative diabetic retinopathy (NPDR) and patients with no apparent diabetic retinopathy (NDR). CONCLUSIONS: TNF-α might be involved in the progression of DR, especially in the pathogenesis of PDR. TNF-α is a potential cytokine for the prognosis of DR and might act as a therapeutic target in DR.